que tenho a dizer sobre mim: a percepção de pré- vestibulandos sobre a própria identidade como brasileiro, jovem, aluno de escola pública e pessoal de baixa renda - Nunes, Hellen dos Santos (2019)
Considering identity is a social construct, the result of several aspects that influence the personal, cultural, social and educational formation of the person, it was intended to verify as pre-university entrance exams of a voluntary preparatory course for public school students understand four identities that coincidentally they are intrinsic to them: brazilian, young, public school student and poor. For this, are analyzed essays produced by pre-university students from themes related to these identities. It is also observed such valuing manifestations are related to the writing process to which students are submitted, not only during the Enem test, but in their school life as a whole. This connection is observed from reports produced on the first day of school, in which students explain their relationship with writing inside and outside the school environment, their educational experience and the feelings that such situations arouse. The reflection on such texts results in the analyzes present in this research, supported by the identity studies by Hall (2006, 2014), Bauman (2005), Silva (2014) and Woodward (2014), and the authorship consideration by Bakhtin (2003), Barthes (2012) and Foucault (2001), expanding the discussion to textual production in school. The results show how the dissertations reproduce some of the stereotypes present in society, especially those defended by the socioeconomically favored strata that intend to maintain themselves as models for the less favored. In addition, it is possible to see how the writing process developed at school is homogenizing, contributing to the perpetuation of prejudice about identities, about the textual production itself and even about the ability of the students themselves.